Assessing the Connection between Nuclear and Renewable Energy on Ecological Footprint within the EKC Framework: Implications for Sustainable Policy in Leading Nuclear Energy-producing Countries - Ivan A. Duran; Saqib, Najia; Haider Mahmood (International Journal of Energy Economics and Policy, 2023)
Numerous Sustainable Development Goals (SDGs) set by the United Nations can’t be completed without switching to alternative energy sources. Countries need to find common ground between energy security, affordability, accessibility, and environmental sustainability if they are to lay the groundwork for competition and success. Considering the connection between economic growth, nuclear power generation, renewable energy consumption, and non-renewable energy usage, this study examines the ecological footprints of leading nuclear energy-producing countries ( the United States, France, China, Russia, Japan, South Korea, Canada, the Ukraine, the United Kingdom, and Germany) from 1990 to 2020. In order to perform such a thorough empirical investigation, this study makes use of advanced econometric methods. According to the long-term cointegration study, environmental quality is negatively impacted by economic growth and the use of non-renewable energy, while it is positively impacted by the square of economic growth, the use of nuclear energy, and the use of renewable energy. The study found that the ecological footprint is directly correlated with both nuclear power and economic growth. Meanwhile, both renewable and non-renewable energy sources were found to have an effect on the ecological footprint in a causal manner. The findings of this study emphasize the significance of the world’s major nuclear energy producing countries harmonizing their energy policies and developing a common energy strategy that includes equitable distribution of key components of the global nuclear energy sector.